Cover Image. (23rd November 2021) - Qin, Tiantian; Zhao, Jinzhu; Liu, Xiaojie; Li, Leilei; Zhang, Xueyan; Shi, Xiaoli; Ke, Yu; Liu, Weihua; Huo, Junfeng; Dong, Yalong; Shen, Yiwei; Li, Yanyu; et al.
Abstract : The cover image is based on the Research Article Luteolin combined with low‐dose paclitaxel synergistically inhibits epithelial–mesenchymal transition and induces cell apoptosis on esophageal carcinoma in vitro and in vivo by Tiantian Qin et al., https://doi.org/10.1002/ptr.7267 . Abstract : The cover image is based on the Research Article Luteolin combined with low‐dose paclitaxel synergistically inhibits epithelial–mesenchymal transition and induces cell apoptosis on esophageal carcinoma in vitro and in vivo by Tiantian Qin et al., https://doi.org/10.1002/ptr.7267 .